Giving Credit Where Credit's Due: Why It's So Hard to Do in Psychological Science. (November 2016) - Simonton, Dean Keith
More than a century of scientific research has shed considerable light on how a scientist's contributions to psychological science might be best assessed and duly recognized. This brief overview of that empirical evidence concentrates on recognition for lifetime career achievements in psychological science. After discussing both productivity and citation indicators, the treatment turns to critical precautions in the application of these indicators to psychologists. These issues concern both predictive validity and interjudge reliability. In the former case, not only are the predictive validities for standard indicators relatively small, but the indicators can exhibit important non-merit-based biases that undermine validity. In the latter case, peer consensus in the evaluation of scientific contributions is appreciably lower in psychology than in the natural sciences, a fact that has consequences for citation measures as well. Psychologists must therefore exercise considerable care in judging achievements in psychological science—both their own and those of others.